HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG PREEKLAMSIA DENGAN KEJADIAN PREEKLAMSIA DI RSKD IBU DAN ANAK PERTIWI MAKASSAR - ANTI, SRI JULIANTI NUR; muaningsih, Muaningsih; asriyanti, Asriyanti (Jurnal Ilmu Keperawatan Komunitas, 2025)
Preeclampsia refers to an acute pregnancy complication and occurs during pregnancy, labor and post-partum periods. Eclampsia is one of the main causes of the maternal death. The preeclampsia occurs prior to the eclampsia and it complicates the pregnancy. Preeclampsia is noticed based on the symptoms such as hypertension associated with proteinuria and edema during pregnancy. This quantitative research employs the design of cross-sectional study. The samples were selected using accidental sampling technique and as many as 55 respondents were included as the samples. The aim of the research was to find out the correlation of the knowledge level of the pregnant mother related to preeclampsia and its occurrence at RSKD Ibu dan Anak Pertiwi of Makassar. Based on the statistical test of Chi-Square, the value of p (0.005) < 0.05. The research hypothesis confirmed that Ha was accepted and HO was rejected, therefore, it showed the correlation of the knowledge level of the pregnant mothers related to the preeclampsia and its occurrence at RSKD Ibu dan Anak Pertiwi of Makassar. The finding presented the significant correlation of the knowledge level of the pregnant mother related to preeclampsia and the occurrence of preeclampsia at RSKD Ibu dan Anak Pertiwi of Makassar.